An annotated catalogue of the Iranian Microtypinae and Rogadinae (Hymenoptera: Braconidae) - Beyarslan, Ahmet; Gadallah, Neveen S.; Ghahari, Hassan (Zootaxa, 2017)
The Iranian species diversity of the braconid subfamilies Microtypinae (four species from one genus, Microtypus Ratzeburg), and Rogadinae (33 species from four genera, Aleiodes Wesmael, Heterogamus Wesmael, Clinocentrus Haliday and Yelicones Cameron) is summarized. A faunistic list is given comprising both local and global distribution of each species as well as host records. In the present study Microtypus trigonus (Nees, 1843) (Microtypinae), Aleiodes albitibia (Herrisch-Schaeffer, 1838) and Aleiodes coxalis (Spinola, 1808) (Rogadinae) are new records for the fauna of Iran.